Hybrid Nanoparticles for Haloperidol Encapsulation: Quid Est Optimum? - Filippov Sergey K; Khusnutdinov Ramil R; Inham Wali; Liu Chang; Nikitin Dmitry O; Semina Irina I; Garvey Christopher J; Nasibullin Shamil F; Khutoryanskiy Vitaliy V; Zhang Hongbo; Moustafine Rouslan I (MDPI, 2022)
The choice of drug delivery carrier is of paramount importance for the fate of a drug in a human body. In this study, we have prepared the hybrid nanoparticles composed of FDA-approved Eudragit L100-55 copolymer and polymeric surfactant Brij98 to load haloperidol-an antipsychotic hydrophobic drug used to treat schizophrenia and many other disorders. This platform shows good drug-loading efficiency and stability in comparison to the widely applied platforms of mesoporous silica (MSN) and a metal-organic framework (MOF). ZIF8, a biocompatible MOF, failed to encapsulate haloperidol, whereas MSN only showed limited encapsulation ability. Isothermal titration calorimetry showed that haloperidol has low binding with the surface of ZIF8 and MSN in comparison to Eudragit L100-55/Brij98, thus elucidating the striking difference in haloperidol loading. With further optimization, the haloperidol loading efficiency could reach up to 40% in the hybrid Eudragit L100-55/Brij98 nanoparticles with high stability over several months. Differential scanning calorimetry studies indicate that the encapsulated haloperidol stays in an amorphous state inside the Eudragit L100-55/Brij98 nanoparticles. Using a catalepsy and open field animal tests, we proved the prolongation of haloperidol release in vivo, resulting in later onset of action compared to the free drug.